2022
DOI: 10.3390/ijerph19031782
|View full text |Cite
|
Sign up to set email alerts
|

The Unified Protocol for Transdiagnostic Treatment of Emotional Disorders in Children (UP-C) in Portugal: Feasibility Study Results

Abstract: The Unified Protocol for Children (UP-C) is a transdiagnostic Cognitive-Behavioral Therapy group intervention for children and caregivers targeting the treatment of children’s emotional disorders (EDs). The present study aims to assess the feasibility and acceptability of the UP-C in the Portuguese population using a single-armed design. The participants were 32 children (6–12 years of age) with an ED (anxiety and/or depressive disorder) as a main diagnosis and their parents. All participants received the UP-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
6
0
4
Order By: Relevance
“…Evidence has revealed that internet-delivered interventions are as efficacious as traditional face-to-face treatments[ 44 , 45 ]. Transdiagnostic, emotion-focused cognitive-behavioral treatments, such as UP for Transdiagnostic Treatment of Emotional Disorders (UP), may be particularly well suited to address the challenges practicing psychologists and their patients face during the current COVID-19 pandemic[ 46 - 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has revealed that internet-delivered interventions are as efficacious as traditional face-to-face treatments[ 44 , 45 ]. Transdiagnostic, emotion-focused cognitive-behavioral treatments, such as UP for Transdiagnostic Treatment of Emotional Disorders (UP), may be particularly well suited to address the challenges practicing psychologists and their patients face during the current COVID-19 pandemic[ 46 - 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 61 ] The findings also suggest that a sustained response to therapy over a three-month follow-up period may come about due to the UP-C, possibly focusing on trans-diagnosis elements, which promotes the knowledge of a range of feelings and symptoms manifestations. [ 49 ] Transdiagnostic interventions often focus on the central processes of emotional disorders, including identifying emotions, their tolerance, and management. [ 62 ]…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an N = 138 with four measurements is sufficient for growth mixture modeling [ 50 ]. With an attrition rate of 15% [ 19 , 51 ], we will have to recruit approximately 165 parents at T0 to achieve the final intended sample size.…”
Section: Methodsmentioning
confidence: 99%